2014
DOI: 10.1371/journal.pone.0110207
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Risk Factors on Different Interval Cancer Subtypes in a Population-Based Breast Cancer Screening Programme

Abstract: BackgroundInterval cancers are primary breast cancers diagnosed in women after a negative screening test and before the next screening invitation. Our aim was to evaluate risk factors for interval cancer and their subtypes and to compare the risk factors identified with those associated with incident screen-detected cancers.MethodsWe analyzed data from 645,764 women participating in the Spanish breast cancer screening program from 2000–2006 and followed-up until 2009. A total of 5,309 screen-detected and 1,653… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 37 publications
5
35
0
1
Order By: Relevance
“…The distribution of tumor characteristics between ICs and non-ICs overall was not in full agreement with other literature, with ICs being larger at diagnosis (Komenaka et al, 2004;Brekelmans et al, 2001), of higher grade (Domingo et al, 2010;Kirsh et al, 2011;Meshkat et al, 2015), and displaying more lymph node involvement (Musolino et al, 2012;Blanch et al, 2014) and more often being ER/PR-negative (Damiani et al, 2015;Musolino et al, 2018), HER2-positive (Martín-López et al, 2012;Musolino et al, 2018), or triple negative (Gilliland et al, 2000). As results, these studies have reported that IC tumors had, on average, a poorer prognosis of ICs than those of screening-detected breast cancers (Andersson et al, 1998;Collett et al, 2005;Sihto et al, 2008).…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…The distribution of tumor characteristics between ICs and non-ICs overall was not in full agreement with other literature, with ICs being larger at diagnosis (Komenaka et al, 2004;Brekelmans et al, 2001), of higher grade (Domingo et al, 2010;Kirsh et al, 2011;Meshkat et al, 2015), and displaying more lymph node involvement (Musolino et al, 2012;Blanch et al, 2014) and more often being ER/PR-negative (Damiani et al, 2015;Musolino et al, 2018), HER2-positive (Martín-López et al, 2012;Musolino et al, 2018), or triple negative (Gilliland et al, 2000). As results, these studies have reported that IC tumors had, on average, a poorer prognosis of ICs than those of screening-detected breast cancers (Andersson et al, 1998;Collett et al, 2005;Sihto et al, 2008).…”
Section: Discussionsupporting
confidence: 40%
“…In concordance with this, Holm et al, (2015) reported a two-fold increase in the odds for ICs among BRCA mutation carriers, in line with our results. Other studies of BRCA mutations have reported a lowered sensitivity of mammography screening for carriers (Brekelmans et al, 2001;Komenaka et al, 2004) Musolino et al, 2012;Blanch et al, 2014) on family history and ICs reports conflicting results, using varying definitions of family history and low patient numbers.…”
Section: Discussionmentioning
confidence: 96%
“…10, 11, 14, 39, 45, 51 The detailed findings, summarised in our results, are complex but reveal some common findings. Mammographic density was consistently associated with occult BCs (followed by true interval BCs) rather than missed interval cases, 10, 14 highlighting a likely masking effect.…”
Section: Discussionmentioning
confidence: 66%
“…Third, to classify BC after FPR as either FNDA or new cancer, we used an algorithm that mainly used location data, which are routinely collected in both the BCR and the screening program. Compared with radiological review of all files, such an algorithm has several important advantages, including avoiding radiologist subjectivity, a much lower workload, and more complete data ( Blanch et al , 2014 ). We cannot exclude that some cases were categorized as FNDA, although these BC were in reality unrelated to the lesion seen at screening, meaning we would overestimate the FNDA rate.…”
Section: Discussionmentioning
confidence: 99%